Pioneering the future of electronic identity: from post-quantum cryptography to fiduciary principles - Schardong, Frederico (2024)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Ciência da Computação, Florianópolis, 2024.